The Rationality of Surabaya State University Students in Choosing Teaching Majors: An Analysis of Max Weber’s Social Action - Sufiyah, Putri Cahya; M. Jacky (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
In everyday life, society views educational activities are unsuitable for men, so women must take over this activity. This perception has gradually led to a clearer division of roles between men and women. During a six-month observation at Surabaya State University, an interesting phenomenon of gender dominance was discovered when the education department had a larger female student population than male students. This study aimed to analyze the reasons given by students for choosing the education department by adopting a qualitative research method. The data sources used are secondary data and primary data. Secondary data comes from books, journals, theses, and documents that still have an appeal to the research topic. Then the primary data is obtained through non-participant observation and unstructured interviews. Furthermore, it is explained using the interactive model data analysis technique from Miles and Huberman. The results of the study indicate that male students decisions to choose the education major were made after considering future job prospects (instrumental rationality), referring to religious values (value rationality), referring to feelings (affective action), and continuing the family tradition of pursuing a career in education (traditional action). Unlike previous studies focusing more on external factors (economic support), this study highlights more complex internal reasons.